Experimental Prototype Model of IDVR for Bidirectional Voltage Compensation - Ramchandra Nittala; Alivelu M. Parimi; K. Uma Rao (Institute of Advanced Engineering and Science, 2018)
Interline Dynamic Voltage Restorer (IDVR) is an optimum solution to compensate voltage sag in multiple lines. The IDVR consisting of two or more DVRs connected to different feeders in a power system sharing a common DC link energy. This paper presents the hardware implementation of novel bidirectional voltage sag compensation by the IDVR in multiple feeders at same instance. A two line feeder power system with IDVR installed is considered. The IDVR is implemented using two VSI with filter. The control system of IDVR is developed using DSPACE 1103.